Estimating Turkish Stock Market Returns with APT Model: Cointegration and Vector Error Correction - Özge Sezgin Alp; Fazil Gökgöz; Güray Küçükkocaoglu (Economic Review: Journal of Economics and Business, 2016)
Multifactor financial models are of great importance in analyzing practical asset prices. As an alternative to CAPM, Arbitrage Pricing Theory (APT), developed by Ross (1976), describes the expected returns on any financial asset with respect to macroeconomic factors. There are limited researches into APT and its applications in emerging markets. In this respect, it is crucial to analyze the Turkish stock market under APT perspective. The goal of this study is to investigate expected returns of Turkish stock market with APT during the period 2000-2012. Eight major indices of Borsa Istanbul (BIST) have been analyzed as benchmarks. The relationship between main stock indices and macroeconomic variables has been submitted to cointegration tests and vector error correction model analyses. The results have revealed that significant macroeconomic variables vary upon sectors and have a long-run effect in determining stock indices. Consequently, it should be noted that empirical tests of APT have robust estimations in analyzing the Turkish stock market.
Keywords: C32; G12; 330; Arbitrage Pricing Theory; Cointegration; Emerging Markets; Turkey